Construction of an Efficient Engineered Strain for Chaetoglobosin A Bioresource Production from Potato Starch Industrial Waste - Kai Zhang; Shanshan Zhao; Zhengran Wang; Ming Cheng; Wan Wang; Qian Yang (Foods)
Chaetoglobosin A (CheA), a typical structure of the cytochalasin family, exhibits outstanding efficacy against a variety of tumor cells and plant pathogens. However, its low yield and high production cost are major obstacles limiting its wide application. In order to increase CheA yield, an engineered strain was established by overexpressing CgMfs, the gene encoding the MFS family’s efflux pump, on chassis cells lacking CgXpp1, which have been shown to act as a negative regulator of CheA biosynthesis. As expected, the engineered strain significantly boosted CheA production from 63.19 to 265.93 mg/L after incubation in PDA medium for 10 d, whereas the yield of the engineered strain was remarkably enhanced 2.93-fold compared with the wild type, following 10 d of cultivation utilizing potato starch industrial waste. The addition of metal ions had a positive effect on CheA production, with Cu2+ being the most effective and improving production to 176.92 mg/L. The optimal fermentation conditions were determined by response surface optimization, and under the optimal conditions, the engineered strain could stably produce CheA with a yield of 197.58 mg/L. This study provided the conditions for reducing production costs while increasing CheA production, as well as new strategies and insights for the production of the target compound.